Tradisi Bebantai di Merangin Jambi, Studi Living Hadis dalam Konteks Budaya Lokal - Baharudin, Baharudin; Baiquni, Ach (Al-Bukhari : Jurnal Ilmu Hadis, 2023)
This article aims to explore the tradition of bebantai in Merangin, Jambi, as a living hadith practice in the local cultural context. Bebantai is a collective ritual of slaughtering buffaloes or cows to welcome the holy month of Ramadan. This tradition has been carried out for generations by the people of Merangin, especially in Pangkalan Jambu subdistrict. The research method used is qualitative with a descriptive-analytical approach. The data sources are primary and secondary data obtained through observation, interviews, and literature review. The data analysis technique uses content analysis. The results show that bebantai is a manifestation of the hadith about the virtue of sacrificing animals in Ramadan and distributing their meat to the needy. Bebantai also reflects the values of gratitude, solidarity, brotherhood, and mutual assistance among the community members. Bebantai is not only a religious ritual but also a cultural expression that preserves the local identity and social harmony.